L’architecte paysagiste à Alger pendant la période coloniale (1830-1962) : une figure émergente - Fares Trodi; Nadia Djelal; Philippe Potié (Projets de Paysage)
The profession of landscape architect does not exist in Algeria today. In spite of the many emblematic landscape development projects that have seen the light of day in Algeria, ranging from the first plantations by French military engineers to the master plan of the city of Constantine, the figure of the landscape designer had difficulty in emerging in Algeria compared with the neighbouring countries of Morocco and Tunisia. Based on an historical approach, this article shows how the figure of the engineer or architect conducting landscape developing projects in Algiers nevertheless emerged up until 1962.